The Effect of Internal Control on Employee Performance at Kiara Resto Ciater SPA Resort Subang West Java - Fazry, Rachma Waty; sukandi, andi (LPPM Akper Kebonjati, 2025)
Writer interested in studying the effects of internal control over employee performance in perennial Kiara Resto Ciater SPA Resort Subang West java, presumably caused by factors in the performance of employees who have not been implemented effectively.The porpose of this study was to determine how much influence the internal control on the performance of employees at Kiara Resto Ciater SPA Resort Subang West java lasting full earring. The author uses a quantitative approach to associative method. Samples used in perennial Kiara Resto Ciater SPA Resort Subang West java earring 41 people. Collection is done by using a questionnaire.Research results explain that the internal control variable turned out to be dominanted by the opinion that agreed to pay into a variable number that is equal to 44.1% majority, the answer that states could not agree by 42.4%, answer 11.5% undecided, and who answered disagree by 2.5%, while that answer strongly disagree none at all 0%. Employee performance variable turns in dominance by the opinion expressed by 47.2% agreed, stating srtongly agree 35.8%, hesitant answers 14.6%, the answers do not agree 2.4% and answered srongly disagree that the number 0%.while the magnitude of the effect if internal control over the performance of employees is 57% and the remeaning 43% in the estimate in influenced by other factors and not investigated further by the researched by other researchers as a benchmark for researched and developed again.Conclusions in this research namely that the prediction of the effect of internal control on employee performance is positive. That is to say, that internal control of an effect on employee performance.